Expert System Delayed Walking in the Toddler - Yogi Wiyandra; Firna Yenila (Jurnal KomtekInfo, 2020)
Delayed walking is a disorder of walking delay in the toddler aged 9-18 months. There are several indicators that cause delays in walking on children including motor, genetic and temperament. These factors are rarely understood by parents. And sometimes the delays seem to be left unchecked and that can cause its own failure. The lack of time to consult with a child specialist has resulted in such cases seeming to be left unchecked. Expert systems are built to provide knowledge to the public about the phenomena of walking delays that occur in children and the causes and solutions that will be obtained by parents. This system was built using a forward chaining method whose data reading was traced to the daily activities of toddlers. This system is designed to adapt information directly from child experts or child specialists who understand firsthand the condition of the child and delayed walking.